Research of Key Techniques of Grid Dispatching and Control System in the Environment of Dispatching and Control Cloud. Issue 5 (August 2020) - Zhao, Pu; Qu, Hanbing; Lin, Qirong; Jia, Yujian; Zhang, Yuying; Wang, Yong
Abstract: The dispatching and control cloud (DCC) is a new technology based on technology like cloud technology, big date, and internet technology, which aims to improve the integrated operation quality of bulk power systems. The application of cloud technology to grid dispatching and control (GDC) system is significant to the management level of dispatching operation of the grid, but will also bring new challenges. Taking the maintenance of data information, the security of network and the control of operation and maintain into consideration, this paper explores the key techniques of GDCS in the environment of DCC, and focus on the scheme to enhance the ability of operation and management of GDC system.